Performance enhancement of a microstrip patch antenna using substrate integrated waveguide frequency selective surface for ISM band applications - Gunes, Filiz; Belen, Mehmet A.; Mahouti, Peyman (WILEY, 2018)
In this work, performance enhancement of a microstrip patch antenna working at ISM band (2.4 GHz) is presented using modified cross shaped Frequency Selective Surface (FSS) constructed on Substrate Integrated Waveguide (SIW). Design optimizations and simulations of both the antennas and FSS are carried out on low-cost FR4 substrate (with (r)=4.4, h=1.58 mm, and tan =0.0035) in the 3D CST MSW environment. In addition, to exhibit merit of using SIW structure, the traditional FSS in the same configuration is also applied and performances of the antennas used FSSs with and without SIW are also simulated and compared in the 3D CST MSW environment. Finally, the proposed model is confirmed by measurements agreed with the theoretical results to have enhanced gain and beam width at the 2.4 GHz bandwidth alongside improvement in the return loss.
Keywords: frequency selective surface; gain enhancement; microstrip patch antenna; substrate integrated waveguide; DISPERSION CHARACTERISTICS; Engineering; Optics